2017
DOI: 10.4103/neuroindia.ni_377_16
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sensory level electrical stimulation of the masseter muscle in early stroke patients with dysphagia: A randomized controlled study

Abstract: SES applied to bilateral masseter muscles may provide an effective treatment for both dysphagia and cognitive function in early stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…Some studies classified adulthood into three stages: early (19–40 years), middle (40–65 years), and older adulthood (≥65 years) 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies classified adulthood into three stages: early (19–40 years), middle (40–65 years), and older adulthood (≥65 years) 23 …”
Section: Resultsmentioning
confidence: 99%
“…Additional evidence that may account for the significant relationship between swallowing and cognition comes from research with motor imagery during swallowing. As noted, the swallowing function has a motor component controlled by the motor and premotor cortex 1,31 . These two areas are essential during motor imagery, which is a cognitive strategy, 32 and influence higher‐level cognitive processing 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in facilitation techniques to increase muscle strength and sensory awareness and to prevent muscle atrophy, thereby improving motor function [ 14 , 15 ]. Recently, several studies have demonstrated that NMES does not only induce the activation of the masticatory muscle [ 16 , 17 ] but is also effective for improving oral functions, including masticatory functions in the oral phase of the swallowing process [ 18 , 19 ], which might be due to cortical excitability and physiological changes induced by NMES.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is reported to be a cause of death with increasing prevalence in aging populations in Turkey, as it is in the world (20). Turkish studies have shown that dysphagia is common in these patients at an early stage and affects patients' quality of life (5,21,22). Therefore, it is also important in Turkey to evaluate stroke patients early and effectively at the bedside.…”
Section: Introductionmentioning
confidence: 99%